Design analysis of boiler header inspection robot MK-02 - Abdul Jalal M.F.; Mohamed Sahari K.S.; Anuar A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Boiler corrosion; Boilers; High temperature corrosion; Image acquisition; Inspection; Intelligent computing; Intelligent systems; Internal corrosion; Robots; Soft computing; Thermoelectric power plants; Critical component; External corrosion; High temperature and high pressure; Inspection procedures; Inspection robots; Lifting mechanisms; Operating condition; Thermal power plants; Machine design